Changes in acromegaly comorbidities, treatment, and outcome over three decades: a nationwide cohort study - Rosendal, Christian; Arlien-Søborg, Mai Christiansen; Nielsen, Eigil Husted; Andersen, Marianne Skovsager; Feltoft, Claus Larsen; Klose, Marianne; Andreassen, Mikkel; Bruun, Niels Henrik; Jørgensen, Jens Otto Lunde; Dal, Jakob (Frontiers in Endocrinology, 2024)
Objective: To study the time-dependent changes in disease features of Danish patients with acromegaly, including treatment modalities, biochemical outcome, comorbidities, with a particular focus on cancer, and mortality. Methods: Pertinent acromegaly-related variables were collected from 739 patients diagnosed since 1990. Data is presented across 3 decades (1990-1999, 2000-2009 and 2010-2021) based on the year of diagnosis or treatment initiation. Results: Adenoma size and IGF-I levels at diagnosis did not differ significantly between study periods. The risk of being diagnosed with diabetes, heart disease, sleep apnea, joint disease and osteoporosis increased from the 1990s to the later decades, while the mortality risk declined to nearly half. The risk of cancer did not significantly change. Treatment changed toward use of more medical therapy, and fewer patients underwent repeat surgeries or pituitary irradiation. A statistically significant increase in the proportion of patients achieving IGF-I normalization within 3-5 years was observed over time (69%, 83% and 88%, respectively). The proportion of patients with three or more deficient pituitary hormones decreased significantly over time. Conclusion: Modern medical treatment regimens of acromegaly as well as increased awareness and improved diagnostics for its comorbidities have led to better disease control, fewer patients with severe hypopituitarism and declining mortality in the Danish cohort of acromegaly patients. The risk of cancer did not increase over the study period.